Drawn by the Current - Green, Jocelyn (Thorndike, Maine : Center Point Large Print, 2022)
"A birthday excursion turns deadly when the SS Eastland capsizes with Olive Pierce and her best friend on board. Hundreds perish during the accident, and its only when Olive herself barely escapes that she discovers her friend is among the victims. In the aftermath of the tragedy, Olive returns to her work at a Chicago insurance agency and is immersed in the countless investigations related to the accident. But with so many missing, there are few open -and-shut cases, and she tries to balance her grief with the hard work of finding the truth. While someone sabotages her progress, Olive accepts the help of newspaper photographer Erik Magnussen. As they unravel secrets, the truths they discover impact those closest to Olive. How long will the disaster haunt her - and how can she help the others find the peace they deserve?"--
Keywords: Eastland (Ship) -- Fiction; Steamboat disasters -- Illinois; Chicago River; Fiction; Shipwrecks -- Illinois; Chicago River; Fiction; Insurance companies -- Employees; Fiction; Chicago (Ill.) -- Fiction; Christian fiction; Historical fiction